Evaluation of the child with syncope. Issue 5 (May 2016) - Parker, Gabrielle; Thakker, Pradip; Whitehouse, William P.
Abstract: Transient loss of consciousness (TLOC) is spontaneous loss of consciousness with complete recovery; there is temporary impairment of brain function associated with loss of awareness, loss of responsiveness, and loss of memory. Syncope is the most common cause of transient loss of consciousness in children. Whilst syncope is potentially easy to understand using applied physiology, therapeutic opportunities are often missed, leading to avoidable morbidity and disability. In this article we will discuss the causes of TLOC and focus on the evaluation and management of syncope and orthostatic intolerance in children and young people.